(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
Penuaan Skin aging is proses a natural process that is accelerated by faktor external factors such as exposure sinar to ultraviolet rays and stres oxidative stress radikal from free radicals. To overcome this , the use bahan of natural ingredients with aktivitas antioxidant activity and stimulan collagen stimulants is a focus in the development kosmetik of antiaging cosmetics. Salah One tanaman of the potential plants is Centella asiatica, which contains senyawa active compounds such as asiaticoside, madecassoside, and asiatic acid. This study ini aims to formulate and evaluate krim wajah antiaging face cream based ekstrak on ethanolic daun extract of Centella asiatica leaf in three variasi concentration variations (1%, 3%, and 5%). Metode The research method yang used was experimental, involving proses the formulation process krim tipe emulsi of oil -in -water emulsion type cream, followed by testing parameter of physical parameters (color, odor, pH, viscosity, daya dispersion, and daya adhesion) and uji aktivitas antioxidant activity test using metode DPPH method and inhibition enzim of elastase and collagenase enzymes. Hasil The results showed that all formulas had stabilitas fisik good physical stability baik during penyimpanan 28 days of storage. The Formula with konsentrasi an extract concentration of 5% (F3) showed aktivitas antioksidan the highest antioxidant activity (IC₅₀: 48 ppm) and kemampuan the most effective ability to inhibit enzymes that destroy the structure of the skin. And Thus, formulasi krim berbasis Centella asiatica-based cream formulations have potensi great potential as antiaging herbal cosmetic preparations antiaging that are effective, safe, and worthy